13th IEEE International Conference on Engineering of Complex Computer Systems (Iceccs 2008) 2008
DOI: 10.1109/iceccs.2008.12
|View full text |Cite
|
Sign up to set email alerts
|

Using AADL to Model a Protocol Stack

Abstract: In recent trends, the Architecture Analysis and Design Language (AADL) has received increasing attention from safety-critical software development industries. Specific about the AADL is its strong syntactic and semantic support for the description of both hardware and software architectures. Considering the existing range of software architectures, we study the support AADL offers for the description of software architecture. As a case study we use an implementation of a UDP/IP protocol stack. Based on our exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…By simply enumerating the wires/connections between resistors/components, we miss the forest for the trees. This leads to architectural designs at a very low level that is not easy to communicate and develop -as [8] found the case to be with AADL. Fig.…”
Section: Support For Complex Connectorsmentioning
confidence: 99%
“…By simply enumerating the wires/connections between resistors/components, we miss the forest for the trees. This leads to architectural designs at a very low level that is not easy to communicate and develop -as [8] found the case to be with AADL. Fig.…”
Section: Support For Complex Connectorsmentioning
confidence: 99%
“…However, the use of basic interaction mechanisms as connectors in an architectural specification makes it difficult to understand what the real protocols in the system are and leads to system specifications that are at a very low level of abstraction, as is the case with AADL [11]. Indeed, designers are forced to incorporate the behaviour of the more complex connectors they wish to use into their components, decreasing their re-use potential and increasing the chance of architectural mismatch [14].…”
Section: Related Workmentioning
confidence: 99%
“…These rely mostly on simple interconnection mechanisms like procedure-calls and provide no support for specifying complex connectors, focusing their attention mostly upon components. The end result is that architectures end up more like low-level designs [11].…”
Section: Introductionmentioning
confidence: 99%
“…By simply enumerating the wires/connections between resistors/components, we miss the forest for the trees. This leads to architectural designs at a very low level that is not easy to communicate and develop -as [Delanote et al, 2008] found the case to be with AADL. Figure 4 shows the number of simple connectors (identified with red ellipses) that are needed in our system.…”
Section: So the Interaction Protocol (Connector) Used Is The One Thatmentioning
confidence: 99%